Endolymphatic sac tumour in von Hippel-Lindau disease: management strategies - Zanoletti, E. (Acta Otorhinolaryngol Ital, 2017)
Endolymphatic sac tumour (ELST) is infrequent, as emerges from small series reported in the literature. It is a slow-growing malignancy with local aggressiveness and a low risk of distant metastases. It is often misdiagnosed because of the late onset of symptoms and difficulty in obtaining a biopsy. Its frequency is higher in von Hippel-Lindau (VHL) disease (a genetic systemic syndrome involving multiple tumours), with a prevalence of around 25%. The diagnosis is based on radiology, with specific patterns on contrast-enhanced MRI and typical petrous bone erosion on bone CT scan. Our experience of ELST in the years between 2012-2015 concerns 7 cases, one of which was bilateral, in patients with VHL disease. Four of the 7 patients underwent 5 surgical procedures at our institution. Each case is described in detail, including clinical symptoms, and the intervals between symptom onset, diagnosis and therapy. Postoperative morbidity was low after early surgery on small tumours, whereas extensive surgery for large tumours was associated with loss of cranial nerve function (especially VII, IX, X). The critical sites coinciding with loss of neurological function were the fallopian canal, jugular foramen, petrous apex and intradural extension into the posterior cranial fossa. Early surgery on small ELST is advocated for patients with VHL disease, in whom screening enables a prompt diagnosis and consequently good prognosis.